2013
DOI: 10.1371/journal.pone.0069872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angle on Flow-Induced Vibrations of Pinniped Vibrissae

Abstract: Two types of vibrissal surface structures, undulated and smooth, exist among pinnipeds. Most Phocidae have vibrissae with undulated surfaces, while Otariidae, Odobenidae, and a few phocid species possess vibrissae with smooth surfaces. Variations in cross-sectional profile and orientation of the vibrissae also exist between pinniped species. These factors may influence the way that the vibrissae behave when exposed to water flow. This study investigated the effect that vibrissal surface structure and orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 25 publications
8
75
1
Order By: Relevance
“…The sensitivity of the seal also overlaps with the signals produced by the vibrissal structure during flow interactions. Excised seal vibrissae produce a distinct low-frequency vibrational signal (<300 Hz) when exposed to low-velocity (0.5 m s −1 ) water flow under laboratory conditions (Murphy et al, 2013). The spectral characteristics of these vibrissal signals correspond closely to the frequency sensitivity of the sensory system revealed by psychophysical testing.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The sensitivity of the seal also overlaps with the signals produced by the vibrissal structure during flow interactions. Excised seal vibrissae produce a distinct low-frequency vibrational signal (<300 Hz) when exposed to low-velocity (0.5 m s −1 ) water flow under laboratory conditions (Murphy et al, 2013). The spectral characteristics of these vibrissal signals correspond closely to the frequency sensitivity of the sensory system revealed by psychophysical testing.…”
Section: Discussionmentioning
confidence: 57%
“…The low absolute detection thresholds measured in the present study demonstrate acute sensitivity of the vibrissal system and highlight the importance of fine-scale vibration detection in seals. Especially sensitive detection capabilities may be of particular importance to seals considering the fact that the morphology and orientation (Murphy et al, 2013) of the vibrissae have been shown to suppress the amplitude of vibration. In the context of this reduced amplitude effect, changes in whisker vibrations caused by encountering a hydrodynamic disturbance while moving through the surrounding fluid present a distinct input signal to the vibrissal system.…”
Section: Relevance To Understanding the Sensory Systemmentioning
confidence: 99%
“…Since then, a few other parties have carried out studies on the vibration properties of seal whiskers on both real and model specimens [91,143,95]. The important thing to note is that none of the experiments that provided quantitative results were conducted under conditions that allowed the whisker to vibrate freely in response to the flow.…”
Section: Other Whisker Vibration Studiesmentioning
confidence: 99%
“…Real whiskers are curved along the span, and it would be good to determine how much the VIV response of the harbor seal whisker changes with the addition of curvature. Footage of swimming harbor seals by [95] led those authors to observe that the major curvature of the hair shaft was generally in the downstream (caudal) direction. In that case, the curvature would likely not dramatically increase the VIV response.…”
Section: Optimizing the Whisker Geometrymentioning
confidence: 99%
See 1 more Smart Citation